Psychosocial therapies in severe mental illness: update on evidence and recommendations. Issue 4 (July 2020) - Gühne, Uta; Weinmann, Stefan; Riedel-Heller, Steffi G.; Becker, Thomas
Abstract : Purpose of review: To provide an overview of the update of the evidence-based and consensus-based German S3 guideline on psychosocial therapies for severe mental illnesses (SMI), with particular attention to current developments and future research tasks. Recent findings: There has been a significant increase in studies on the effectiveness of psychosocial interventions in treatment of people with SMI. In the guideline a distinction is made between system-level interventions (e.g. multidisciplinary team-based psychiatric community care) and single-handed (nonteam-based) interventions (e.g. psychoeducation). Furthermore, principles of treatment (e.g. recovery-orientation) and self-help interventions (e.g. peer support) are addressed. The update of the guideline includes 33 recommendations and 12 statements. Compared with the first edition, there were upgrades in the recommendation of Supported Employment (A) and Supported Housing (A). Interventions such as peer support (B) and lifestyle interventions (A) were included for the first time. Developments are discussed in the context of most recent literature. Areas for further research are highlighted and fields for next updates such as antistigma interventions and supported parenting were identified. Summary: The present guideline offers an important opportunity to further improve health services for people with SMI. However, guideline implementation is challenging.